Wawasan Kebangsaan pada Layanan Pendidikan Keagamaan Umat Konghucu di Lembaga Litang Cibinong - Elma Haryani; Syahrul Adam; Muhammad Murtadlo (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
The Chinese ethnic group is recognized as one of Indonesia's ethnic groups, and even the Confucian religion is accommodated and served by the state. However, some people often question the Indonesian nationalism of the Chinese ethnic groups. This study aims to examine the national insight of the Chinese Confucians in the context of religious education services at the Litang institution. This research uses a qualitative study, with a case study approach to Litang Cibinong Bogor, West Java. Data collection was carried out by conducting visitations, in-depth interviews and literature reviews. This study found that Confucians felt that they had a higher sense of nationalism compared to Chinese ethnic groups outside of Confucianism. However, they admit that nationality material has not been included in their religious education curriculum design. It is due to the presence of religion and religious, educational institutions that are still new. They are more preoccupied with various problems in Religious Education services that are still far from standards, such as regulatory issues, human resources, and lack of services. Government intervention to give equal attention to all religious adherents will develop Indonesian-minded religious education for Confucians in the future.